ANALISIS KETERAMPILAN PASSING BAWAH BOLA VOLI PADA SISWA KELAS X1 AGRIBISNIS TERNAK RUMINANSIA SMK NEGERI 1 BAWEN - Azwan, Muhamad; Ratimiasih, Yulia; Prastiwi, Bertika Kusuma (YLPK Mahardhika, 2024)
This study aims to analyze the underhand passing skills in volleyball among 11th-grade students of the Agribusiness of Ruminant Livestock class at SMK Negeri 1 Bawen, as many students still struggle to perform accurate ball passes during underhand passing to their teammates. The research employs a quantitative approach using a survey method and an instrument like a volleyball underhand passing assessment rubric. The research sample consists of all 34 students in the 11th grade. Data were analyzed descriptively and presented in percentages. The study results indicate that the majority of students (88%) fall into the